2000
DOI: 10.1038/sj.ijir.3900517
|View full text |Cite
|
Sign up to set email alerts
|

Corporeal counter incisions: a simplified approach to penile prosthesis implantation in fibrotic cases

Abstract: Objective: To evaluate the effectiveness of the technique of corporeal counter incisions for penile prosthesis implantation in cases with marked corporeal ®brosis. Methods: Creating subtunical tunnels that are stretched transversely by the dilamezinsert instrument & Heggars dilators with its tip entering from one side and protruding from the counter incision to avoid urethral or corporeal perforation. Patients: Seventeen patients underwent this technique, mean age 56 y (range 42 ± 71 y); 12 post removal of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Dilatation of the crura was performed via the proximal corporotomy, separate from dilatation of the distal corpora cavernosa (via the distal corporotomy), thus shortening the distance that the dilator had to travel unseen. This, in addition to the lateral orientation of dilatation away from the urethra, helped avoiding injury [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dilatation of the crura was performed via the proximal corporotomy, separate from dilatation of the distal corpora cavernosa (via the distal corporotomy), thus shortening the distance that the dilator had to travel unseen. This, in addition to the lateral orientation of dilatation away from the urethra, helped avoiding injury [3].…”
Section: Discussionmentioning
confidence: 99%
“…Although this method provides better control and safer dilatation, nevertheless, the dilators still traveled blindly and against resistance, although for half a phallus at a time. The authors reported that expanding the subtunical tract was usually very difficult at the start, but with persistent and patient dilatation, the fibrous tissue gradually yielded [3].…”
Section: Discussionmentioning
confidence: 99%
“…The subcutaneous tissue was closed using 4-0 dyed vicryl and the skin was closed using subcuticular undyed vicryl stitch and SteriStrips [13] . The incision was subcoronal in all cases except one with corporeal fibrosis which needed counter-incisions [14] .…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…1 Although Fishman described various techniques for corporeal reconstruction for complicated penile implants well, implantation of a penile prosthesis into a severe corporeal fibrosis is not always successful. 2,3 We implanted inflatable prosthesis in a patient with severe corporeal fibrosis, which was dissected and removed by electric resection and evaporization unit.…”
Section: Introductionmentioning
confidence: 99%